Prism Inside: Spectroscopic and Magnetic Properties of the Lanthanide(III) Chloride Oxidotungstates(VI) Ln3Cl3[WO6] (Ln = La – Nd, Sm – Tb). Issue 21 (20th October 2017) - Dorn, Katharina V.; Blaschkowski, Björn; Förg, Katharina; Netzsch, Philip; Höppe, Henning A.; Hartenbach, Ingo
Abstract : The lanthanide(III) chloride oxidotungstates(VI) with the formula Ln 3 Cl3 [WO6 ] for Ln = La – Nd, Sm – Tb were synthesized by solid‐state reactions utilizing the respective lanthanide trichloride, lanthanide sesquioxide (where available), and tungsten trioxide together with lithium chloride as flux. The title compounds crystallize hexagonally in space group P 63 / m (no. 176, a = 941–909, c = 543–525 pm, Z = 2). The structures comprise crystallographically unique Ln 3+ cations surrounded by six O 2– and four Cl – anions (C.N. = 10) forming distorted tetracapped trigonal prisms as well as rather uncommon trigonal prismatic [WO6 ] 6– units, whose edges are coordinated by nine Ln 3+ cations. Thus, a 3 ∞ ([WO6 ] Ln e 9/3 ) 3+ framework ( e = edge‐sharing) is created, which contains tube‐shaped channels along [001] lined with chloride anions. To elucidate the spectroscopic and magnetic properties of the obtained pure phase samples, single‐crystal Raman (for Ln = La – Nd, Sm–Tb), diffuse reflectance (for Ln = La, Pr, Nd, Gd), and luminescence spectroscopy (for bulk Ln 3 Cl3 [WO6 ] ( Ln = La, Eu, Gd, Tb) and Eu 3+ ‐ or Tb 3+ ‐doped derivatives of La3 Cl3 [WO6 ] and Gd3 Cl3 [WO6 ], respectively) were performed and their temperature‐dependent magnetic moments (for Ln = Pr, Nd, Gd) were determined. Abstract :